Analysis Location Quotient Analysis in Determining Leading Horticulture Products in Ngawi District - Putra, Mohammad Edwinsyah Yanuan; Dhandy, Rahmat; Al Ayyubi, Waridad Umais; Sholihah, Elis Rahmawati Mar’atus; Firman, Anwar; Alwirya, Ngani; Wardana, Aditya (Pascasarjana, Mataram University, 2024)
The agricultural sector is one sector that has great potential to improve the economy. To increase the role of the government and the income of fruit and vegetable farmers, the government and farmers need to better manage their business results for marketing or sale. The level of welfare of fruit and vegetable farmers is still low, this is not because the selling price of fruit and vegetables is low, nor is it because of the large number of imported fruit and vegetables, but rather because of the government's lack of attention to the fruit and vegetable sub-sector, especially durian. snakefruit. Oranges, bananas, mangoes and papaya. This research used a descriptive method, which was carried out in Ngawi Regency. The selection of the research area and determination of samples was carried out deliberately. Data collection uses the interview method using questionnaires to obtain primary data and documentation methods to obtain secondary data. The data analysis method uses qualitative and quantitative descriptive analysis using the Location Quotient approach which tests the validity of the data using methods, sources and theories. The results of the research show that the factors that have a real influence on the income of fish farmers in Nagari Andaleh, Luak District, Limapuluh Kota Regency, are the leading commodities for the Fruits and Vegetables sub-sector, namely Salak with an LQ value of 4.19 and Durian with an LQ value of 2.36. Other types of commodities such as Oranges with an LQ value of 0.64 also have the potential to be developed, in contrast to non-seeded commodities, namely Bananas with an LQ value of 0.03, Mangoes with an LQ value of 0.05 and Papaya with an LQ value of 0.06.